APLIKASI GELOMBANG ULTRASOUND PADA TONGKAT PUTIH UNTUK PERINGATAN DINI BAGI PENYANDANG TUNA NETRA - M Ary Heryant0; Herwin Suprijono (JURNAL DIAN, 2011)
A cane that is usually used by they visually impaired person called as white cane.lt is a mechanic tool to detect the things on the ground, uneven surfaces, holes, Â stairs,puddles and other obstructions. The problem of using the cane is the users should actively use it to grope anything infront of him. The cane can not detect the other obstruction which is far from the users and it absolutely makes the users uncomforted.Another problem is the white cane just only can detect by groping or tactile objects.The application of ultrasound wave on white cane for the visually impaired person is based on sonar to detect any obstruction toward the man. Thris researchconsisfs of three sfeps; analysis, implementation and evaluation.The result shows that this cane provides a vibration as early information about the object which are about 240 inches from the man. lt will also strongly vibrate when the obstruction is less than 40 inches.Keywords: white cane, visually impaired, early warning, sonar, ultrasound.